'Men of iron will': Idealized gender in Christian heavy metal. (December 2015) - Rademacher, Heidi E
The borders between sacred and secular music are often believed to be fixed and impenetrable. However, when a secular musical genre is reworked for consumption by religious audiences, a space is created where the sacred meets the secular, and this can be used to examine the variety of ways in which cultural norms, values, and ideologies fluctuate and converge between the religious and temporal spheres. In this article, the author looks at the overlapping of Christian and secular heavy metal music, focusing on the ways gender is described, celebrated, and normalized in the lyrics of Christian metal. After analyzing the lyrics of 351 Christian heavy metal songs, she conducts an in-depth analysis of three sets of lyrics. Despite the obvious antithesis between the worlds of heavy metal music and evangelical Christianity, her analysis highlights one avenue where the sacred and secular merge. The display, production, and management of gender can be viewed as a common trope that links Christian metal to secular metal and can function as a means of creating a space for the alignment of religious beliefs within the larger cultural expectations of gender.